2005
DOI: 10.1037/0882-7974.20.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Psychological Well-Being in Advanced Age: A Meta-Analysis of Intervention Studies.

Abstract: A meta-analysis examined data from 36 studies linking physical activity to well-being in older adults without clinical disorders. The weighted mean-change effect size for treatment groups (d(C). = 0.24) was almost 3 times the mean for control groups (d(C). = 0.09). Aerobic training was most beneficial (d(C). = 0.29), and moderate intensity activity was the most beneficial activity level (d(C). = 0.34). Longer exercise duration was less beneficial for several types of well-being, though findings are inconclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

40
520
5
35

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 773 publications
(600 citation statements)
references
References 64 publications
40
520
5
35
Order By: Relevance
“…A meta-analysis examined data from 36 studies linking physical activity with well-being in older adults without clinical disorders. The result showed that aerobic training was most beneficial for several types of well-being, and moderate intensity activity was the most beneficial activity level [4] . Moreover, Colcombe S et al also provided convincing evidence that aerobic fitness training in older persons improved cognitive function, especially executive-control processes.…”
Section: Exercise Induces Psychological and Cognitive Improvements Rementioning
confidence: 97%
“…A meta-analysis examined data from 36 studies linking physical activity with well-being in older adults without clinical disorders. The result showed that aerobic training was most beneficial for several types of well-being, and moderate intensity activity was the most beneficial activity level [4] . Moreover, Colcombe S et al also provided convincing evidence that aerobic fitness training in older persons improved cognitive function, especially executive-control processes.…”
Section: Exercise Induces Psychological and Cognitive Improvements Rementioning
confidence: 97%
“…In a meta-analysis of prospective cohort studies of patients with coronary heart disease, smoking cessation reduced total mortality by 36%. 69 The pleiotropic effects of physical activity (eg, improved lipid profiles, BP, glucose-insulin homeostasis, endothelial function, inflammatory markers, and psychological well-being) [70][71][72][73] likely account for 30% to 50% reductions in incident type 2 diabetes and coronary heart disease in physically active vs sedentary individuals. 72 Diet can reduce death from coronary heart disease by up to 36% and can improve many established risk factors.…”
Section: Treatment Additional Cardiovascular Evaluation and Referralmentioning
confidence: 99%
“…However, secondary analyses differ in their findings on which moderators influence the relation between exercise and SWB in which way. Schlicht's [6] meta-analysis, for example, found a stronger relation for women than men (r women 0.33 vs. r men 0.08), whereas Netz et al [7] found no impact of gender on effect sizes but an effect of age instead: Those aged 54-64 years profited more (d00.33) than those aged 65-74 years (d00.20), and these, in turn, more than the over-74s (d00.11). Nonetheless, both authors show more agreement over the type of exercise: Schlicht [6] reported the largest effect sizes for endurance sports (r00.22), and Netz et al [7] found comparatively high effect sizes for aerobic exercise (d00.29).…”
mentioning
confidence: 99%
“…Schlicht's [6] meta-analysis, for example, found a stronger relation for women than men (r women 0.33 vs. r men 0.08), whereas Netz et al [7] found no impact of gender on effect sizes but an effect of age instead: Those aged 54-64 years profited more (d00.33) than those aged 65-74 years (d00.20), and these, in turn, more than the over-74s (d00.11). Nonetheless, both authors show more agreement over the type of exercise: Schlicht [6] reported the largest effect sizes for endurance sports (r00.22), and Netz et al [7] found comparatively high effect sizes for aerobic exercise (d00.29).Eur Rev Aging Phys Act (2012) 9:87-102 DOI 10.1007/s11556The heterogeneity of findings in primary studies and the inconsistencies in meta-analyses hardly permit any clear statements on which forms of exercise promote well-being. As Ekkekakis and Backhouse [9] have shown for exemplary secondary analyses, a comparative inspection of the same literature can even lead to contradictory conclusions.…”
mentioning
confidence: 99%
See 1 more Smart Citation